(untitled) (Bangladesh Journal of Pathology, 2010)
Key words: Sjogren’s syndrome; Matrixmetalloproteinases (MMPS);Proinflammatory cytokines DOI: 10.3329/bjpath.v24i2.4113 Bangladesh J Pathol 24(2): 15-20